Mechanisms of explicating ethno-cultural aura of an autochthonous and translated text - Shakhputova З.Х.; Alefirenko Н.Ф.; Nurtazina М.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The article deals with the problem of perception and understanding of ethno-cultural aura in literary text. It is proved that the perception of literary text as a set of ethno-linguistic images requires the recipient’s emotional and intellectual inclusion in a mental dialogue with the text’s autochthonous world. The importance of subject-sensory perception for adequate interpretation of the text’s conceptually significant meanings is emphasized. The concepts “qonyr kuz” and “aq zhauyn” are represented by ethno-linguistic images radiating autochthonous aura. Perception occurs through comprehension of linguistic means creating in imagination object-sensory images. Attention is focused on creating ethno-linguistic images of autochthonous literary text in the story and on cognitive-metaphorical origins of its ethno-cultural aura. The analysis showed that text understanding is a step-by-step process, including emotional and sensory perception of the image at sensations’ level, experience as text perception based on subjective life experience (incorporating it in own semantic space), and interpretation as mental decomposition of integral text into its components and mental connection of these components into a whole. The linguoculturological interpretation of the key concepts “zhauyn”, “qonyr”, “kuz” revealed the individual author’s meaning of the discourse-generating concept «qonyr kuz», which is metaphorically disclosed in text through the image of white rain (aq zhauyn). The visual-expressive means of language contributing to the embodiment of the considered ethno-linguistic images are determined. The analysis made it possible to identify the conceptual metaphor «life is a winding road» implicitly presented in the text as the most important constituent of the story’s narrative discourse.